1981
DOI: 10.1002/bjs.1800680813
|View full text |Cite
|
Sign up to set email alerts
|

The microflora of the postoperative stomach

Abstract: The microflora and pH have been assessed in gastric aspirates from 163 patients after gastric surgery and have been compared with 51 patients with gastro-oesophageal carcinoma, 152 unoperated patients with peptic ulceration, 72 of whom were receiving cimetidine, 3 patients with pernicious anaemia and 27 normal subjects. The total viable bacterial count was closely related to the pH of the aspirate and was independent of the cause of the hypochlorhydria; 90 per cent of aspirates of pH 1--2 were sterile, while 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
3

Year Published

1984
1984
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 19 publications
1
23
0
3
Order By: Relevance
“…Mais recentemente, chamou-se a atenção para a relação entre gastrite alcalina e H.pylori 37,38 . Estudos em seres humanos mostraram que a flora bacteriana do estômago após gastrectomia produz maior quantidade de nitrosaminas, que estão, sabidamente relacionadas ao desenvolvimento de câncer gástrico 33 . [42][43][44] , esta correlação vem se tornando cada vez mais forte também quanto ao adenocarcinoma, particularmente do tipo intestinal de Lauren.…”
Section: Métodounclassified
See 1 more Smart Citation
“…Mais recentemente, chamou-se a atenção para a relação entre gastrite alcalina e H.pylori 37,38 . Estudos em seres humanos mostraram que a flora bacteriana do estômago após gastrectomia produz maior quantidade de nitrosaminas, que estão, sabidamente relacionadas ao desenvolvimento de câncer gástrico 33 . [42][43][44] , esta correlação vem se tornando cada vez mais forte também quanto ao adenocarcinoma, particularmente do tipo intestinal de Lauren.…”
Section: Métodounclassified
“…O estudo da microbiota do estômago operado revela aumento do número de bactérias capazes de produzir nitrosaminas 33 . Silva 50 mostrou não só um aumento da população bacteriana do coto gástrico, como uma relação desta com o tipo de reconstrução.…”
Section: Métodounclassified
“…But the etiology and exact mechanism of gastric stump carcinogenesis are unclear. Decreased sensitivity of chief cells and parietal cells [7] , alteration in gastrin level [8] , hypoxia and hemodynamic changes [9] , bacterial proliferation [10] , and reflux [11,12] are the putative contributing factors. Among these, the excessive duodenal reflux induced by surgery seems to be the main risk factor, because the incidence of stump carcinomas is higher in Billroth II than in Billroth I [13,14] , and most of the stump carcinomas are located near the stoma [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown an increased incidence of gastric cancer in areas with high nitrate concentrations in water and soil (Hill et al, 1973;Cuello et al, 1976;Haenszel et al, 1976) and clinical studies have shown increased intragastric nitrite levels in at-risk patients such as those with previous gastrectomy (Jones et al, 1978;Schlag et al, 1980) or pernicious anaemia (Bartholomew et al, 1980). Hypochlorhydria encourages intragastric bacterial proliferation (Ruddell et al, 1976); intraluminal bacteria (Reed et al, 1981) and nitrite (Muscroft et al, 1981;Stockbrugger et al, 1982;MiltonThompson et al, 1982) increase directly with gastric pH.…”
mentioning
confidence: 99%
“…Increased levels of N-nitroso compounds have been reported after Billroth II (Polya) resection (Schlag et al, 1980;Reed et al, 1981) and vagotomy (Reed et al, 1981), in patients with pernicious anaemia (Reed et al, 1981) and in those treated with cimetidine (Stockbrugger et al, 1982) or omeprazole (Sharma et al, 1984). Other workers, however, have not confirmed these findings (Muscroft et al, 1981;MiltonThompson et al, 1982;Keighley et al, 1984). The discrepancy may reflect methodological differences, for example in the sampling and collection of gastric juice and the analysis of N-nitroso compounds (Clark et al, 1985).…”
mentioning
confidence: 99%